Connections between cells of the internal capsule, thalamus, and cerebral cortex in embryonic rat. - Molnár, Z; Cordery, P (1999)
The aim of our study is to understand the development of the earliest connections in the mammalian pallium by documenting the distribution of cells and fibres labelled from the dorsal and ventral thalamus, internal capsule, perirhinal, and dorsal cortex during the period between embryonic day (E) 14 and 17 by using carbocyanine dye tracing in fixed embryonic rat brains. Dye placed in the thalamus of E14 brains backlabels cells in the thalamic reticular nucleus and within the primitive internal capsule. Both anterograde and retrograde tracing confirmed that the first corticofugal projections reach the internal capsule by E14. At E15-E16, after the first cortical plate cells have migrated into the lateral cortex, some cells of the cortical plate and subplate and marginal zone, are backlabelled from the internal capsule, but still not from the dorsal thalamus, even with very long incubation periods. Crystal placement into the perirhinal cortex at E14-E15 labels numerous cells within the internal capsule, whereas no such cells are revealed from dorsal cerebral cortex until E17, suggesting that internal capsule cells establish early connections with the perirhinal and ventral but not dorsal cortex. We propose that the growth of axons from cortex to dorsal thalamus is delayed in two regions: first from E14-E15 at the lateral entrance of the internal capsule and then, from E16, closer to the thalamus, probably within the thalamic reticular nucleus. Subplate projections reach the proximity of the diencephalon at an early stage, but they might never enter the dorsal thalamus.